Flow of lubricated granular material on an inclined plane - Ghodake, Ravindra S.; Doshi, Pankaj; Orpe, V. Ashish (Powder Technology, 2022)
We have studied the gravity driven flow of spherical shaped, millimetric sized granular material coated with aspherical, micron-sized, near frictionless lubricant particles. Experiments were performed on an inclined plane using two different sized particles for varying concentrations of the lubricant. The particle volumetric flow rate exhibits a non-monotonic behavior with increasing lubricant concentration. It shows an increase at lower lubricant concentration followed by a decrease at higher lubricant concentration. The lubricant particles adhere to the granular particle surface thereby reducing the inter-particle friction. However, presence of lubricant particles at higher concentration damps out inter-particle collision thereby reducing the inter-particle momentum transfer. Non-monotonicity in the observed behavior is then conjectured to arise due to competing effects of inter-particle friction and inter-particle collision. The present work and the overall observed behavior therein provides a simple experimental system to characterize the effects of added lubricant material in pharmaceutical and other relevant industrial applications.
Keywords: Friction; granular; Inclined plane; Lubrication; Powder